The readiness of public schools for teacher leadership from the perspective of teachers and principals: An input to teacher leadership development program (TLDP) - Gojo Cruz, Mariel Gia V. (Animo Repository, 2020)
The current study determined the teacher leadership readiness of five public high schools in the different districts in Bulacan. This study proposed a teacher leadership program that can be integrated with the School Learning Action Cell (SLAC) sessions to develop and practice the teacher leadership skills of teachers. The study employed a mixed method of research design, specifically the methodological triangulation approach in data gathering, where a blended qualitative and quantitative approach was used. The collected qualitative data complemented and clarified the quantitative findings in helping to identify common responses of teachers and principals. The quantitative part is the survey of 197 public school teachers and five principals from the five participating public schools. The findings showed that in general, the principals and teachers agreed that teacher leadership will help public schools for both students' success and school improvement. However, there are aspects of school culture that need to be addressed to assist the teachers in practicing their teacher leadership. On the other hand, the qualitative part of the study employed an interview with the five principals and a focus group discussion (FGD) with the four teachers nominated by their principals. The results showed the need for teacher leadership programs because it will hone the teachers’ leadership potentials and develop the essential qualities of a teacher leader that public schools nationwide can benefit from. Keywords: Teacher Leadership, teacher leadership program, public high schools, public school teachers, principals